Internal Auditors’ Fraud Detection: A Phenomenological Study - Ida Fatmawati Ar'Reza; Cipto Wardoyo; Sheila Febriani Putri (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2020)
The purpose of this study is to find out the meaning of fraud for internal auditors and what they experience in detecting it. This is a qualitative research using interpretive paradigm with phenomenological methods. The data of this study are the results of observations and interviews with internal auditors in a state-owned company in East Java, and internal audit charter documentations. Based on the results of the interview, four conclusions from the research results are drawn. First, internal auditors literally interpret fraud and as an occupational task focusing on the internal control. Second, fraud detection is more accurately described as fraud potential detection, in which they can find redflag or fraud indication during the inspection with Risk Based Internal Audit method. Legitimacy Theory is the basis when the auditors have gained legitimacy from fraud meaning and detection, since it is in accordance with their roles, activities and competencies in carrying it out.